PENERAPAN MEDIA BUKU PINTAR DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPA TEMA 3 SUB TEMA 1 DI SD NEGERI 4 KLAMBU - Syalma Alfina; Choirul Huda; Prasena Ariyanto (STKIP Subang, 2022)
The background of the problem in this research is the lack of variation in the learning process of fourth grade students. This is caused by the learning that is used less in the use of media in learning so that it is less than optimal. The purpose of this study is to find out how the application of Smart Book Media in Improving Student Learning Outcomes in Science Subjects Theme 3 Sub Theme 1 at SD Negeri 4 Klambu. The type of this research is quantitative research with experimental research method and using One-Group Pretest-Posttest design. Based on the results of the research which includes the formulation of the problem, hypothesis, data analysis, and discussion, it can be concluded that there is an increase in learning outcomes using Smart Book Media. In addition, it can also increase the activeness of students in the learning process, thereby increasing learning outcomes in understanding the material. The samples taken were 26 fourth grade students at SDN 4 Klambu using the Nonprobability Sampling technique. The data in this study were obtained through observation, tests and documentation. The results of the study after receiving treatment showed an increase in student learning outcomes seen from the results of the pretest and posttest. the average pretest value is 44.6154 and the posttest average value is 67.5385. Based on the initial normality test of 4.2 Lo = 0.092 and N = 26 with a significant level of 5%, the L table is 0.173. So Lo < Ltable or (0.092 < 0.173) then Ho is accepted. while the final normality test was 4.3 Lo = 0.143 and N = 26 with a significant level of 5%, obtained Ltable = 0.173. So Lo < Ltable or (0.143 < 0.173) then Ho is accepted